Anti-phase domains in cubic GaN - Maria Kemper, Ricarda; Schupp, Thorsten; Häberlen, Maik; Niendorf, Thomas; Maier, Hans-Jürgen; Dempewolf, Anja; Bertram, Frank; Christen, Jürgen; Kirste, Ronny; Hoffmann, Axel; Lindner, Jörg; As, Donat (Journal of Applied Physics)
The existence of anti-phase domains in cubic GaN grown on 3C-SiC/Si (001) substrates by plasma-assisted molecular beam epitaxy is reported. The influence of the 3C-SiC/Si (001) substrate morphology is studied with emphasis on the anti-phase domains (APDs). The GaN nucleation is governed by the APDs of the substrate, resulting in equal plane orientation and the same anti-phase boundaries. The presence of the APDs is independent of the GaN layer thickness. Atomic force microscopy surface analysis indicates lateral growth anisotropy of GaN facets in dependence of the APD orientation. This anisotropy can be linked to Ga and N face types of the {111} planes, similar to observations of anisotropic growth in 3C-SiC. In contrast to 3C-SiC, however, a difference in GaN phase composition for the two types of APDs can be measured by electron backscatter diffraction, μ-Raman and cathodoluminescence spectroscopy.

Epitaxial growth and interfacial magnetism of spin aligner for remanent spin injection: [Fe/Tb]n/Fe/MgO/GaAs-light emitting diode as a prototype system - Schuster, E.; Brand, R. A.; Stromberg, F.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Wende, H.; Keune, W. (Journal of Applied Physics)

Characterization of unintentional doping in nonpolar GaN - Zhu, Tongtong; Johnston, Carol F.; Häberlen, Maik; Kappers, Menno J.; Oliver, Rachel A. (Journal of Applied Physics)
Unintentional doping in nonpolar a-plane 112¯0 gallium nitride GaN grown on r-plane 11¯02 sapphire using a three-dimensional 3D–two-dimensional 2D growth method has been characterized. For both 2D only and 3D–2D growth, the presence of an unintentionally doped region adjacent to the GaN/sapphire interface is observed by scanning capacitance microscopy SCM. The average width of this unintentionally doped layer is found to increase with increasing 3D growth time. By using an intentionally doped GaN:Si staircase structure for calibration, it is shown that the unintentionally doped region has an average carrier concentration of 2.50.31018 cm−3. SCM also reveals the presence of unintentionally doped features extending at 60° from the GaN/sapphire interface. The observation of decreasing carrier concentration with distance from the GaN/sapphire interface along these features may suggest that the unintentional doping arises from oxygen diffusion from the sapphire substrate. Low temperature cathodoluminescence spectra reveal emission peaks at 3.41 and 3.30 eV, which are believed to originate from basal plane stacking faults BSFs and prismatic stacking faults PSFs, respectively. It is shown that the inclined features extending from the GaN/sapphire interface exhibit both enhanced BSF and PSF emission. We suggest that enhanced unintentional doping occurs in regions around PSFs. Where BSFs intersect this doped material their emission is also enhanced due to reduced nonradiative recombination. Transmission electron microscopy confirms the presence of PSFs extending through the film at 60° from the GaN/sapphire interface.

Low temperature photoluminescence and cathodoluminescence studies of nonpolar GaN grown using epitaxial lateral overgrowth - Häberlen, M.; Badcock, T. J.; Moram, M. A.; Hollander, J. L.; Kappers, M. J.; Dawson, P.; Humphreys, C. J.; Oliver, R. A. (Journal of Applied Physics)
Low temperature cathodo- and photoluminescence has been performed on nonpolar a-plane GaN films grown using epitaxial lateral overgrowth. In films overgrown at a low V–III ratio, the emission spectrum is dominated by “yellow” and “blue” luminescence bands, attributed to recombination at point defects or impurities. The intensity of this emission is observed to decrease steadily across the window region along the −c direction, possibly due to asymmetric diffusion of a point defect/impurity species. When overgrown at a higher V–III ratio, the near band edge and basal-plane stacking fault emission intensity increases by orders of magnitude and a donor–acceptor pair band is observed. Using monochromatic cathodoluminescence imaging, the various emission features are correlated with the microstructure of the film. In particular, the peak energy of the basal-plane stacking fault emission is seen to be blueshifted by 15 meV in the wing relative to the window region, which may be related to the different strain states in the respective regions.

Electroconvection of liquid crystals: Tool for fabricating modulated polymer surfaces - Hoischen, A.; Benning, S. A.; Kitzerow, Heinz-Siegfried (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Silicon nanoparticles: Absorption, emission, and the nature of the electronic bandgap - Meier, Cedrik; Gondorf, Andreas; Lüttjohann, Stephan; Lorke, Axel; Wiggers, Hartmut (Journal of Applied Physics)

Vibrational and defect states in SnOx nanoparticles - Meier, Cedrik; Lüttjohann, Stephan; Kravets, Vasyl G.; Nienhaus, Hermann; Lorke, Axel; Ifeacho, Pascal; Wiggers, Hartmut; Schulz, Christof; Kennedy, Marcus K.; Kruis, F. Einar (Journal of Applied Physics)

Spin injection light-emitting diode with vertically magnetized ferromagnetic metal contacts - Gerhardt, N. C.; Hövel, S.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Halm, S.; Bacher, G.; Westerholt, K. (Journal of Applied Physics)

Space charge field and dynamics of the grating formation in a photorefractive polymer-dispersed liquid crystal based on a photoconducting polysiloxane - Paelke, Lutz; Kitzerow, Heinz-Siegfried (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Magnetic and chemical properties of Co[sub 2]MnSi thin films compared to the Co[sub 2]MnSi∕Al-O interface - Schmalhorst, J.; Sacher, Marc; Höink, V.; Reiss, G.; Hütten, A.; Engel, D.; Ehresmann, A. (Journal of Applied Physics)
Keywords: General Physics and Astronomy